Intervalos de referência dos parâmetros de volume plaquetário: Estudo Longitudinal de Saúde do Adulto Minas Gerais (ELSA-MG) - Chams Bicalho Maluf (2011)
Introduction and objective: The development of automated hematology analyzers made possible the automatic measurement of various parameters of platelet volume, such as mean platelet volume (MPV), platelet distribution width (PDW) and platelet large cell ratio (P-LCR). Since these parameters had become available in the 70s, many studies to define its utility and significance had been published. Over the past two years, there was an increasing number of literatures that correlates the platelet parameters to cardiovascular and cerebrovascular diseases. The standardization of preanalytical and analytical factors and determination of reference intervals is essential for the clinical use of these parameters. Thus, the aim of this study was to determine the reference range of parameters of platelet volume in participants from the Longitudinal Study of Adult Health (ELSA-MG). Methods: 173 subjects were selected among ELSA-MG according to established criteria based on the recommendations of the Clinical and Laboratory Standards Institute (CLSI). All procedures were standardized based on these recommendations: analysis of equivalence or reciprocal of equipments used and hematological interfering preanalytical factors (storage time and used anticoagulant) prior to data collection. The values distribution of all parameters were analyzed and the limits and reference intervals were defined using non parametric test. Results: The analysis showed that the results from different equipments used in the study were equivalent, the use of ethylenediaminetetraacetic acid (EDTA) as anticoagulant showed time-dependent increase in the values of the parameters of platelet volume. The distribution of results was a normal or Gaussian distribution, and reference interval obtained was: MPV 8,9 a 12,2 fL; PDW 9,4 a 16,0; P-LCR 15,8 a 41,6 Conclusions: Analysis of the tests showed that equipments could be used interchangeably, and the time for the analysis of specimens collected in EDTA were standardized. The reference intervals for the parameters of platelet volume were defined, and can be used to follow-up ELSA-MG participants to assess possible correlation with subsequent atherothrombotic events. Key words: Platelets, parameters of platelet volume, reference intervals